Divergent effects of Tlr9 deletion in experimental late venous thrombosis resolution and vein wall injury - Dewyer, Nicholas A.; El-Sayed, Osama M.; Luke, Catherine E.; Elfline, Megan; Kittan, Nicolai; Allen, Ron; Laser, Adriana; Oostra, Carson; Comerota, Anthony; Hogaboam, Cory; Kunkel, Steven L.; Henke, Peter K. (Thrombosis and Haemostasis, 2015)
Deep-vein thrombosis (DVT) resolves via a sterile inflammatory response. Defining the inflammatory response of DVT may allow for new therapies that do not involve anticoagulation. Previously, we have shown that Toll-like receptor 9 (Tlr9) gene deleted mice had impaired venous thrombosis (VT) resolution. Here, we further characterise the role of Tlr9 signalling and sterile inflammation in chronic VT and vein wall responses. First, we found a human precedent exists with Tlr9+ cells present in chronic post thrombotic intraluminal tissue. Second, in a stasis VT mouse model, endogenous danger signal mediators of uric acid, HMGB-1, and neutrophil extracellular traps marker of citrullinated histone-3 (and extracellular DNA) were greater in Tlr9-/- thrombi as compared with wild-type (WT), corresponding with larger VT at 8 and 21 days. Fewer M1 type (CCR2+) monocyte/macrophages (MØ) were present in Tlr9-/- thrombi than WT controls at 8 days, suggesting an impaired inflammatory cell influx. Using bone marrow-derived monocyte (BMMØ) cell culture, we found decreased fibrinolytic gene expression with exposure to several endogenous danger signals. Next, adoptive transfer of cultured Tlr9+/+ BMMØ to Tlr9-/- mice normalised VT resolution at 8 days. Lastly, although the VT size was larger at 21 days in Tlr9-/- mice and correlated with decreased endothelial antigen markers, no difference in fibrosis was found. These data suggest that Tlr9 signalling in MØ is critical for later VT resolution, is associated with necrosis clearance, but does not affect later vein wall fibrosis. These findings provide insight into the Tlr9 MØ mechanisms of sterile inflammation in this disease process.
Keywords: Animal models; deep-vein thrombosis; inflammation; venous thrombosis